2016
DOI: 10.1007/s12571-016-0566-x
|View full text |Cite
|
Sign up to set email alerts
|

The nutrition transition and indicators of child malnutrition

Abstract: Abstract. We analyze how the nutrition transition affects child malnutrition in developing countries. It is often assumed that the nutrition transition affects child weight but not child growth, which could be one reason why child underweight decreases faster than child stunting.But these effects have hardly been analyzed empirically. Our cross-country panel regressions show that the nutrition transition reduces child underweight, while no consistent effect on child overweight is found. Against common views, o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 46 publications
(80 reference statements)
1
7
0
Order By: Relevance
“…To gain a broader understanding, we compiled country-level panel data from a large number of developing countries and ran additional cross-country regressions. This cross-country analysis suggests that the share of supermarkets in national food retailing is negatively associated with both child underweight and child stunting (58) , which supports the micro-level evidence from Kenya.…”
Section: Proceedings Of the Nutrition Societysupporting
confidence: 75%
“…To gain a broader understanding, we compiled country-level panel data from a large number of developing countries and ran additional cross-country regressions. This cross-country analysis suggests that the share of supermarkets in national food retailing is negatively associated with both child underweight and child stunting (58) , which supports the micro-level evidence from Kenya.…”
Section: Proceedings Of the Nutrition Societysupporting
confidence: 75%
“…Compared to traditional food markets in developing countries, supermarket supply chains are often more efficient, which can make food more accessible for poor population segments [ 21 , 25 , 32 ]. Recent studies showed that supermarkets can contribute to reduced rates of child undernutrition in some situations [ 32 , 62 ]. Food quality, food diversity, and food safety may also be higher in supermarkets than in traditional markets [ 30 , 35 , 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nineteen of the reviewed studies (21%) analysed data from multiple countries. The studies with the most extensive geographic scope covered 166 countries (Smith and Haddad 2015), 63 countries (Smith and Haddad 2001), and 41 countries (Kimenju and Qaim 2016). The analysis in each of these studies was conducted at the country level.…”
Section: Geographical Coveragementioning
confidence: 99%